RANCANG BANGUN SISTEM INFORMASI KEPUASAN PETANI TERHADAP KINERJA PENYULUH PERTANIAN BERBASIS WEBSITE DI BALAI PENYULUHAN PERTANIAN SITUBONDO - Firman Jaya; Puryantoro Puryantoro (AMIK Mitra Gama, 2022)
Agricultural extension plays a very important role in agricultural development. The availability of extension workers in a village does not guarantee that they can provide the same results because it depends on how the extension workers can provide satisfaction to farmers with the resulting performance. The purpose of this research is to produce an information system of farmer satisfaction on the performance of agricultural extension workers based on the website.The research was conducted at the Agricultural Extension Center - Department of Agriculture and Food Security, Situbondo. The research method used in this study was the Research and Development method. Data were collected by means of interviews to determine the aspects that will be raised in the questionnaire in the farmer satisfaction system. The data is then made a system design which is then implemented into a programming language to express the results of the system design. To check that the requirements are appropriate and running as desired, the system testing process is carried out. Based on the results of testing the system already includes the need for evaluation of agricultural extension workers